Synchronous generator stabilization by thyristor controlled supercapacitor energy storage system - Hossain, Md Rishad; Hossain, Md Kamal; Ali, Mohd Hasan; Luo, Yusheng; Hovsapian, Rob (Proceedings of IEEE Southeastcon, 2017)
A thyristor-controlled supercapacitor energy storage (SES) system is proposed in this work to improve the transient stability of a synchronous generator located in a power network. To check how effective the proposed SES in augmenting the transient stability of the generator is, its performance is compared to that of a thyristor-controlled superconductive magnetic energy storage (SMES) system. Both symmetrical and unsymmetrical faults are considered in the power network. Simulation results demonstrate the effectiveness and validity of the proposed method in enhancing the transient stability of the synchronous generator. Moreover, the performance of proposed SES is found to be better than that of SMES. Overall, it can be inferred that the proposed thyristor-controlled SES technique provides a simple and effective means of transient stability improvement of synchronous generator.